THE MEDIATING ROLE OF COGNITIVE FLEXIBILITY BETWEEN FOREIGN LANGUAGE LEARNING MOTIVATION AND FOREIGN LANGUAGE ANXIETY OF UNIVERSITY PREPARATORY SCHOOL STUDENTS - Çetin, Çağlar; Bölükbaşı Macit, Zerrin (International Online Journal of Education and Teaching, 2022)
The aim of this study is to reveal the mediating role of cognitive flexibility of university preparatory students between their foreign language learning motivation and foreign language anxiety. The sample of the study consists of 314 volunteer students over the age of 18 and from different language levels who are studying in the English preparatory program of the Department of Foreign Languages ​​of Eskişehir Osmangazi University in the spring term of the 2018-2019 academic year. The data of the study were collected with the "Foreign language classroom anxiety scale FLCAS)", "Cognitive flexibility inventory (CFI)", "Foreign language learning motivation scale (FLLMS)". According to the mediation test findings; It has been found that cognitive flexibility has a statistically full mediator role in the relationship between Foreign Language Learning Motivation and foreign language anxiety. Accordingly, foreign language learning motivation negatively predicts foreign language anxiety through cognitive flexibility. Preparatory students with high motivation to learn foreign languages ​​also have high cognitive flexibility and as a result, their foreign language anxiety is lower.